Taxonomic review of the genera Balistoides, Pseudobalistes and Parabalistes of the family Balistidae with redescription of species occurring in Indian Seas - Sahayak, Satish; Joshi, K. K.; Sriramachandra Murty, V. (Indian Journal of Fisheries, 2014)
Fish samples under the the three genera Balistoides, Pseudobalistes and Parabalistes of the family Balistidae were collected from Kalpeni, Minicoy, and Agatti islands of Lakshadweep seas and also from Tuticorin, Keelakarai and Mandapam along the south-east-coast of India during 2000-2002. The studies on these three genera revealed variation of colour pattern in fishes collected from south-east coast as well as from Minicoy. Parabalistes Bleeker, 1866 which was earlier considered to be a synonym of genus Pseudobalistes has been resurrected as a valid genus. Two species of genus Balistoides and one species each of Pseudobalistes and Parabalistes reported and redescribed in the present study from the Indian seas are Balistoides viridescens (Bloch and Schneider, 1801), Balistoides conspicillum (Bloch and Schneider, 1801), Pseudobalistes flavimarginatus (Ruppell, 1828) and Parabalistes fuscus (Bloch and Schneider, 1801).